Principles for the pastoral guidance process to women on matters related to human vulnerability and personal integrity - Plessis, Amanda L. du (HTS teologiese studies, 2015)
Through the centuries, women from all over the world remain vulnerable to their social status. In some developed countries the situation has improved, but there are many countries where it is still unbearable. United Nations Educational, Scientific and Cultural Organization (UNESCO) aims to assist in this regard by addressing ethical issues pertaining to medicine, life sciences and related technologies as applied to human beings with consideration of women’s social, legal and environmental dimensions. Yet pastoral counsellors on ground level are confronted with the need for assistance to women who suffer because of this exploitation. Therefore, the aim of this article is to focus on biblical principles that can serve as anchors to guide women regarding their human vulnerability and personal integrity when they experience suffering and hardship. The challenge facing the pastoral counsellor is to guide women to accept the reality of their situation within a certain framework, to adequately deal with this and, in spite of overwhelming emotions, continue to grow in personal integrity and healing.